Empathic Professional Competence Through A Deontological and Islamic Values-Based Pedagogical Model - Shahlo Isamiddinovna Botirova; Mukhlisa Dustnazar Omonova (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
The growing complexity of social interaction, digitalized learning environments, and ethical challenges in contemporary education has intensified the need for teachers who demonstrate not only pedagogical competence but also strong empathic and moral responsibility. This demand is particularly salient in Islamic educational institutions, where teachers are expected to embody ethical conduct, compassion (rahmah), and professional accountability grounded in Islamic values. This study aims to design and qualitatively examine a deontologically grounded pedagogical model for developing empathic professional competence among prospective teachers in Islamic higher education. Adopting a qualitative research design, the study integrates pedagogical modeling with classroom observations and semi-structured reflective interviews involving pre-service teachers and teacher educators in Islamic higher education institutions. Data were analyzed using thematic analysis to explore how empathic professional competence was internalized, enacted, and reflected upon within authentic teaching contexts. The findings reveal three interrelated themes: internalization of moral duty as a professional obligation, growth of empathic sensitivity toward students’ cognitive and emotional needs, and enhanced ethical reflection in pedagogical decision-making. These findings indicate that the deontological and Islamic values-based pedagogical model supports the holistic formation of empathic professional competence by fostering ethical awareness, reflective judgment, and morally grounded teaching practices. In conclusion, the study offers a theoretically grounded qualitative framework for strengthening teacher preparation in Islamic education, with practical implications for cultivating ethically responsible, empathetic, and reflective educators in madrasah, pesantren, and Islamic higher education institutions.